Penggunaan Edible Coating dari Pektin dan Kitosan untuk Meningkatkan Kualitas Buah Pepaya (Carica Papaya L) Potong - Muryeti, Muryeti; Azhari, Giattika; Tasyamara, Alsya; Ningtyas, Rina; Silvia, Deli (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Muryeti, M., Giattika, A., Alsya, T., Rina, N., & Deli, S. (2024). Use of edible coating from pectin and chitosan to improve the quality of fresh cut papaya (Carica Papaya L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 398–408). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Papaya (Carica papaya L ) is a type of climateric fruit that physical and chemical properties changes quickly and decreasing quality. Edible coating made from orange pectin and chitosan is expected to increase the shelf life of papaya. The aimed of this research was to determine the effect of pectin and chitosan in improving the quality of fresh cut papaya. The research stages was making and applying edible coating from various of chitosan (0.5%, 1,5% and 2%), and testing weight loss, acifity level (pH) and vitamin C content. Then the data obtained were analyzed using ANOVA and DMRT. Characteristic of papaya that has been applied with edible coating able to reduce weight loss, maintain the TDS value, vitamin C and increasing the shelf life. At cold temperature, chitosan concentration had a significant effect on weight loss percentage and pH, while pectin and chitosan concentration had a significant effect on TPT value. The edible coating could protect the quality of papaya during storage at cold temperature (100C) for 12 days. The weight loss percentage reached 14.95%, the pH was 3.5, TPT was 5.2 °Brix , vitamin C level was 24,75 mg/100g. Edible coating with the concentration of chitosan of 2% can maintain the quality and shelf life of fresh cut papaya during storage.